Comparative investigation of 'survival' and fatality factors in accidental residential fires. (April 2015) - Xiong, Lin; Bruck, Dorothy; Ball, Michelle
Abstract: Objective: This study compares the odds ratio (OR) values of factors associated with accidental residential fires where an individual has died versus fires where all occupants have survived (with no serious injury that required extended hospitalisation). Methods: Analyses were based on 177 single fatalities (from coronial files) and 183 survivors (from interviews) of accidental residential fires. Results/discussion: The top seven risk factors (OR>10) that were significantly more associated with fatal than survived fires were, in descending order, psychotropic and sedative drug intake, discarded cigarettes, living alone, being aged over 70, being asleep, location in the room of fire origin (RFO) at ignition, and alcohol intake. The five risk factors (OR>10) that were more significantly associated with survived fires were, in descending order, cooking fires, electrical fires, kitchen being RFO, stove being an appliance involved in ignition, and fire in a one or two family dwelling. People who survived were more likely to wake up to non-smoke alarm fire cues (e.g. glass breaking, smoke) than a smoke alarm cue. Conclusions: This comparative study provides new insights into statistically significant differences in risk factors between fatal fires and those fires where all occupants survived. The implications for fire engineering are complex as most fatal residential fires were associated with cognitive and physical impairment. Highlights: Odds ratios differ significantly between fatal and survived accidental residential fires. Top risk factors of fatal fires were drugs, smoking-related, living alone, aged 70+ and asleep. Top risk factors of survived fire were cooking-related activities and electrical failure.